Physico-Chemical Properties and Microbial Biomass Carbon of Bamboo Growing Soils: A Comparative Study - Gogoi, Bhabesh; Bhuyan, T. C. (Indian Forester, 2016)
Bamboo can regenerate very fast without replanting and is highly effective in restoring soil degradation. However, impacts of bamboos on soil properties differ at species level. Therefore, the present study was undertaken to quantify and to make a comparative assessment in the status of soil properties after 12 years of bamboo plantations. In the study, significant variations were observed in physico-chemical properties viz. bulk density, water holding capacity, pH, electrical conductivity and organic carbon of soil. Soil available N,P and K were increased over initial in case of all bamboo species under study.Result revealed that the soil microbial biomass carbon measurements ranged between 294 and 510 Î¼g/g, which represented 2.00 to 3.47%of total organic carboninsoil. The present paper describes in detail the physico-chemical and biological properties of soil as affected by 12 year plantations of 10 different bamboo species in an Inceptisol of Assam, India.